Cesar Millan's lessons from the pack : stories of the dogs who changed my life - Millan, Cesar; Peltier, Melissa Jo (National Geographic, 2017)
Looks at the positive effects that having and training dogs has on their owners, and shares personal stories of how the dogs in his life have given him important lessons in respect, confidence, resilience, and authenticity.